Antioxidant-Rich Pedada Fruit Scrub Innovation (Natural Beauty Secrets From The Coast) - Novi Andriana; Mega Lusiana Sitorus; Juli Nurhaliza; Nisa Ulzannah (Universitas 17 Agustus 1945 Semarang, 2024)
Dead skin cells can occur due to many factors, such as increasing age, sun exposure, and an unhealthy lifestyle. Signs of skin problems due to the buildup of dead skin cells are dull skin, acne, and dry skin. Body scrub is a type of skin care that can provide many benefits for skin health and beauty. Scrub is the process of exfoliating dead skin cells using a scrub or natural ingredients. Pedada fruit scrub is a natural beauty care innovation originating from the coast of Indonesia, especially from areas rich in pedada fruit plants (Sonneratia spp.). Pedada fruit is known to have high antioxidant content which can provide benefits for the skin, such as brightening it, reducing wrinkles, and fighting the effects of free radicals. This scrub uses pedada fruit extract which is rich in flavonoids, tannins and vitamin C to care for the skin naturally. This body scrub product not only offers beauty benefits but is also environmentally friendly because the raw materials are easy to find in coastal areas and do not require complicated chemical processes. This research aims to examine the benefits of pedada fruit scrub as a natural beauty solution that is rich in antioxidants.